Buku Profil Penyelidikan Skim Geran Penyelidikan Fundamental (Frgs) - Ghazali, Arniza
The end-of-life of the non-recyclable EFB alkaline peroxide fibres was extendable when the mechanisms of harvesting the nano-structured cells were elucidated. Through 17000 kWh/mt mechanical shearing impact, cells of 5 nm to 100 nm thickness peeled. The energy intensiveness can be resolved by supercritical fluid extraction of radical treated EFB. The cells with 60% crystallinity blended cellulose, auxochromes, xylan and nano-minerals, accounted for the 24% enhanced softness. Registered as ‘TRX-cellsⓇ, the cells portray affinity for colours, enabling precision printing when coated on commercial A4 paper and delivery of plant pigments to the grain core. The cells cascading mechanism fulfills a closed-loop process, demonstrating the actualisable circular nano technology in EFB utilisation, harmonising people-nature-technology coexistence through an accentuated profit for sustainability